High-strength Cu-Zr binary alloy with an ultrafine eutectic microstructure - Kim, Kyou-Hyun; Ahn, Jae-Pyoung; Lee, Jae-Hoon; Lee, Jae-Chul (CAMBRIDGE UNIV PRESS, 2008)
In this study, we synthesized Cu-Zr binary alloys reinforced with an ultrafine eutectic microstructure. The alloys consisted of alternating layers of a hard superlattice phase and a ductile Cu phase with a very fine interlamellar spacing of similar to 60 nm. The superlattice phase enhanced the strength of the alloys while the laminated composite structure helped improve their plasticity, making their mechanical properties comparable to those of the earlier reported high strength alloys. This paper discusses the fundamental microstructural aspects that influence the mechanical properties of these alloys.
Keywords: NANOSTRUCTURE-DENDRITE COMPOSITE; BULK METALLIC GLASSES; TI; PLASTICITY; DUCTILITY